2021
DOI: 10.3390/su13116491
|View full text |Cite
|
Sign up to set email alerts
|

Issues Surrounding Behavior towards Discarded Textiles and Garments in Ljubljana

Abstract: In recent years, post-consumer textile waste has become an important issue that attracts attention from activists, scientists and the media. The production and use of clothing has more than doubled in the last fifteen years due to declining costs, streamlined operations and rising consumption under the influence of fast fashion. According to research, the average European buys as much as 26 kg of textiles each year and discards 11 kg, while a very small share of post-consumer textile waste is recycled. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…These data highlight the lack of systems improving MTW capture and information helping citizens make a more appropriate decision when discarding MTW, although the Waste Directive 2018/851 sets that all Member States must ensure separate collection of textiles by 2025 (European Parliament and Council of the European Union, 2018). Moreover, previous studies have already investigated citizens' behaviour and management of MTW at a regional level and highlighted low collection of SMTW as a key factor influencing the environmental impacts of the textile industry (Laitala, 2014;Nencková et al, 2020;Polajnar Horvat and Šrimpf Vendramin, 2021). Analogously, this paper aims to shed light on MTW management practices by citizens in Catalonia.…”
Section: Case Study: Mtw Management In Cataloniamentioning
confidence: 88%
“…These data highlight the lack of systems improving MTW capture and information helping citizens make a more appropriate decision when discarding MTW, although the Waste Directive 2018/851 sets that all Member States must ensure separate collection of textiles by 2025 (European Parliament and Council of the European Union, 2018). Moreover, previous studies have already investigated citizens' behaviour and management of MTW at a regional level and highlighted low collection of SMTW as a key factor influencing the environmental impacts of the textile industry (Laitala, 2014;Nencková et al, 2020;Polajnar Horvat and Šrimpf Vendramin, 2021). Analogously, this paper aims to shed light on MTW management practices by citizens in Catalonia.…”
Section: Case Study: Mtw Management In Cataloniamentioning
confidence: 88%
“…There are differences in people's knowledge and purchasing decisions related to lack of consistency in information. Targeted information dissemination, education, and other practical social impact methods can improve people's understanding and awareness, resulting in appropriate changes in practice [22][23]. Information provision and greater attention both from consumers and service providers could be a significant input, especially to food waste reduction in the public catering service sector [24].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies demonstrated the importance of apparel sustainability knowledge and personal values (Su et al, 2019), green knowledge (Khare and Kautish, 2021), environmental awareness (Polajnar Horvat and Šrimpf Vendramin, 2021), and attitude towards sustainable textile products (Rausch and Kopplin, 2021) and awareness of eco-fashion (Cairns et al, 2022).…”
Section: Knowledge and Experiencementioning
confidence: 99%